Innovative Practices as a Key for a Better Management in Tourism Industry - Tsonev, Nikolay; Kaleychev, Svetoslav (European Journal of Economics and Business Studies, 2018)
The dynamics in socio-economic life raises the need of new organizational and managerial solutions that meet the requirements of contemporary society. Innovative technologies, as part of these solutions, have a major impact on all areas of life and determine the direction of social development. Modern managers and leaders in the economic industry strive to implement the best innovation practices that will be the key for achieving of the maximum results and ultimate goals. In this respect, tourism as a sector of global economic and social importance is aware of the need to implement innovative practices in all tourism activities. International tourism market show specific changes in the actual and potential tourist behavior. These changes are significant and affect all of the participants in the process of formation and realization of the tourism products, producers and distributors. The main goal is connected with the achieving of a more personal experience, inner satisfaction and maximum recovery as expression of the global contemporary trends in the tourism business. In a more dynamic competitive environment, participants in the tourism market must increasingly rely on the implementation and use of innovative technologies that improve management, organizational structure, economic policy and contributing for the success of the tourism companies.